Thermal conductivity of calcium carbonate filled with unsaturated polyester composites with different filler sizes - Mahshuri, Y.; Amalina, M.A.; Nadhirah, C.A.N. (Maney Publishing, 2014)
The effect of filler size to the thermal conductivity of the calcium carbonatefilled with unsaturated polyester composites has been experimentally investigated. The filler was derived from the shell of local clam known as Polymesoda bengalensis. Neat unsaturated polyester samples and calcium carbonate filler with eight different mean diameter sizes were embedded in the unsaturated polyester with 8 wt-% filler loading. Thermal conductivity was measured by applying the guarded heat flow meter method according to ASTM E1225-99 using P. A Hilton Heat Conduction Unit H-940. The result shows that at constant filler content, the thermal conductivity of calcium carbonate/unsaturated polyester composites were increased gradually as the filler size was decreased.